Antibodies against Pneumococcal Capsular Polysaccharides and Natural Anti-Galactosyl (Alpha-Gal) in Patients with Humoral Immunodeficiencies - Kralickova, P; Kuhnova, J; Soucek, O; Vodarek, P; Zak, P; Simkovic, M; Motyckova, M; Smolej, L; Mala, E; Andrys, C; Krejsek, J; Thon, V (Journal of immunology research, 2017)
Humoral deficiencies represent a broad group of disorders. The aim of the study was to compare the levels of antibodies against pneumococcal capsular polysaccharides (anti-PCP) and natural anti-galactosyl (anti-Gal) antibodies in (1) patients with chronic lymphocytic leukaemia (CLL), (2) patients with common variable immunodeficiency (CVID), and (3) a healthy population and to explore their diagnostic and prognostic potential. Serum immunoglobulin levels and levels of anti-Gal IgG, IgA, and IgM and anti-PCP IgG and IgG2 were determined in 59 CLL patients, 30 CVID patients, and 67 healthy controls. Levels of IgG, IgA, IgM, anti-Gal IgA, anti-Gal IgM, and anti-PCP IgA were lower in CLL and CVID patients than in healthy controls (p value for all parameters < 0.0001). Decrease in the levels of IgA, IgM, anti-Gal IgA, and anti-PCP IgA was less pronounced in the CLL group than in the CVID group. IgA decline, anti-Gal IgA, anti-PCP IgA, and anti-PCP IgG2 were negatively correlated with CLL stage. We devise the evaluation of anti-Gal antibodies to be a routine test in humoral immunodeficiency diagnostics, even in cases of immunoglobulin substitution therapy. Significant reductions, mainly in anti-Gal IgA, IgM, and anti-PCP IgA levels, may have prognostic importance in CLL patients.
Keywords: Young Adult; Immunoglobulin G; Male; biologické markery; bakteriální pouzdra; galaktosylceramidy; Autoantibodies; Immunoglobulin M; mladý dospělý; Biomarkers; Pneumococcal Infections; Adolescent; imunoglobulin M; prognóza; Adult; imunoglobulin G; dospělí; Aged; mužské pohlaví; senioři; Galactosylceramides; běžná variabilní imunodeficience; Common Variable Immunodeficiency; Bacterial Capsules; mladiství; senioři nad 80 let; lidé; ženské pohlaví; humorální imunita; Humans; autoprotilátky; Streptococcus pneumoniae; Aged, 80 and over; imunoglobulin A; protilátky bakteriální; Prognosis; pneumokokové infekce; Female; Immunity, Humoral; Immunoglobulin A; lidé středního věku; Antibodies, Bacterial; Middle Aged